The Secondary Metabolite Profiling, Antioxidant, Antidiabetic, Antimicrobial and Acute Oral Toxicity Analysis of Methanol Extract of Elaeocarpus Angustifolius Blume Flower - Pandey, Ram Darash; Joshi, Susan (Journal of Institute of Science and Technology, 2025)
In the present research, we investigated the flowers of the plant Elaeocarpus angustifolius Blume. This plant is cultivated in the hilly regions of Nepal, primarily for its beads. This is the first attempt to study in Nepal to explore the methanol extract of flower using both qualitative and quantitative analyses. The secondary metabolite screening indicated alkaloids, flavonoids, polyphenols, saponins, glycosides, terpenoids, and reducing sugars in the extract.  Several of these metabolites were also confirmed by the GC-MS analysis. The phenolics and flavonoids were quantified by colorimetric tests using the Folin-Ciocalteu reagent (FCR) and AlCl3, respectively. The amount of phenolic and flavonoids in the extract was 169.111 ± 18.867 mg GAE/g at a concentration of 0.644 and 84.401 ± 6.204 mg QE/g at a concentration of 0.582, respectively. The extract was analysed for antioxidant activity by the well-known DPPH method. The IC50 value obtained was 70.659 µg/mL, indicating it to be a moderate antioxidant. The extract was also analysed for antidiabetic potential using the α-amylase inhibition assay. The IC50 value obtained was 1717.0 µg/mL, indicating its weak antidiabetic action. Antibacterial and antifungal activity effect against tested pathogenic bacteria and fungi were not observed. The flower extract and powder were evaluated for acute oral toxicity in Albino mice by OECD guidelines. They were found to be non-toxic.  Due to the high level of phenolic and flavonoid in the extract, this study highlights its potential therapeutic uses for treating diabetes, obesity and antioxidant.